Fuzzy model for assessment of comfortable conditions during design of air conditioning systems - Бабич, Николай Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
The primary and highly important step in the process of designing individual objects and their systems is developing the Terms of Reference (TOR) for design. The most important requirement for the TOR lies in its completeness. The more detailed information the mechanical engineer obtains, the more certain timeframes and quality of design will be. Today, when designing air conditioning and humidification (C&H) systems, most engineers use regulatory documents. But it is becoming increasingly important to take into account individual characteristics of a person during the formation of comfortable conditions parameters. It should be noted that there are many individual parameters and it is quite difficult to define clearly the required vector of such parameters, as well as the values for each of them; hence, a fuzzy logic method should be applied. As a result of simulation, a fuzzy model was developed for assessing comfort conditions in living accommodations. Fuzzy model will greatly improve the quality of design works, namely the formation of technical documentation about design objects